Effect of Reversed Jigsaw Instructional Strategy on Pupils Academic Achievement in Mathematics - Kayode Ezecheal Obafemi; Ayodele Fajonyomi; Eniola Keji Ola-Alani (Universitas Pendidikan Indonesia (UPI), 2023)
The study examined the effect of reversed jigsaw instructional strategy on pupils’ academic achievement in Mathematics. The study adopted a quasi-experimental research design. Two public primary schools were randomly selected to participate in the study. One validated and reliably tested research instrument titled ‘Mathematics Achievement Test’ (MAT) was used. The reliability index of MAT was determined using Pearson Product Moment Correlation (PPMC). Two research hypotheses were formulated and tested at a standard level of significance with an Analysis of Covariance (ANCOVA). The findings of the study revealed that treatment had a significant effect on pupils’ academic achievement in mathematics. However, the interaction of treatment and gender did not have any significant effect on pupils’ academic achievement. Based on the findings, it was concluded that reversed jigsaw instructional strategy can improve the academic achievement of pupils. Based on the conclusion, it was recommended that teachers should be trained in the use of the strategy.